The Receptor Kinase IMPAIRED OOMYCETE SUSCEPTIBILITY1 Attenuates Abscisic Acid Responses in Arabidopsis . Issue 3 (1st October 2014) - Hok, Sophie; Allasia, Valérie; Andrio, Emilie; Naessens, Elodie; Ribes, Elsa; Panabières, Franck; Attard, Agnès; Ris, Nicolas; Clément, Mathilde; Barlet, Xavier; Marco, Yves; Grill, Erwin; et al.
Abstract : An Arabidopsis receptor-like kinase negatively regulates abscisic acid signaling and promotes infection by filamentous (hemi)biotrophs . Abstract: In plants, membrane-bound receptor kinases are essential for developmental processes, immune responses to pathogens and the establishment of symbiosis. We previously identified the Arabidopsis ( Arabidopsis thaliana ) receptor kinase IMPAIRED OOMYCETE SUSCEPTIBILITY1 (IOS1) as required for successful infection with the downy mildew pathogen Hyaloperonospora arabidopsidis . We report here that IOS1 is also required for full susceptibility of Arabidopsis to unrelated (hemi)biotrophic filamentous oomycete and fungal pathogens. Impaired susceptibility in the absence of IOS1 appeared to be independent of plant defense mechanism. Instead, we found that ios1-1 plants were hypersensitive to the plant hormone abscisic acid (ABA ), displaying enhanced ABA -mediated inhibition of seed germination, root elongation, and stomatal opening. These findings suggest that IOS1 negatively regulates ABA signaling in Arabidopsis. The expression of ABA -sensitive COLD REGULATED and RESISTANCE TO DESICCATION genes was diminished in Arabidopsis during infection. This effect on ABA signaling was alleviated in the ios1-1 mutant background. Accordingly, ABA -insensitive and ABA -hypersensitive mutants were more susceptible and resistant to oomycete infection, respectively, showing that the intensity of ABA signaling affects the outcome of downy mildew disease. Taken together, our findings suggest that filamentous (hemi)biotrophs attenuate ABA signaling in Arabidopsis during the infection process and that IOS1 participates in this pathogen-mediated reprogramming of the host.